Breast milk and in utero transmission of HIV-1 select for envelope variants with unique molecular signatures. Issue 1 (December 2017) - Nakamura, Kyle; Heath, Laura; Sobrera, Edwin; Wilkinson, Thomas; Semrau, Katherine; Kankasa, Chipepo; Tobin, Nicole; Webb, Nicholas; Lee, Benhur; Thea, Donald; Kuhn, Louise; Mullins, James; et al.
Abstract Background Mother-to-child transmission of human immunodeficiency virus-type 1 (HIV-1) poses a serious health threat in developing countries, and adequate interventions are as yet unrealized. HIV-1 infection is frequently initiated by a single founder viral variant, but the factors that influence particular variant selection are poorly understood. Results Our analysis of 647 full-length HIV-1 subtype C and G viral envelope sequences from 22 mother–infant pairs reveals unique genotypic and phenotypic signatures that depend upon transmission route. Relative to maternal strains, intrauterine HIV transmission selects infant variants that have shorter, less-glycosylated V1 loops that are more resistant to soluble CD4 (sCD4) neutralization. Transmission through breastfeeding selects for variants with fewer potential glycosylation sites in gp41, are more sensitive to the broadly neutralizing antibodies PG9 and PG16, and that bind sCD4 with reduced cooperativity. Furthermore, experiments with Affinofile cells indicate that infant viruses, regardless of transmission route, require increased levels of surface CD4 receptor for productive infection. Conclusions These data provide the first evidence for transmission route-specific selection of HIV-1 variants, potentially informing therapeutic strategies and vaccine designs that can be tailored to specific modes of vertical HIV transmission.